Dictionary of advertising and marketing concepts - Berger, Arthur Asa, 1933- (Left Coast Press, 2013)
"From AdBusters to viral marketing, this brief dictionary of ideas and concepts contains over 100 extended, illuminating entries to bring the novice up to speed on the advertising/marketing world and the ideas that underlie it. For the neophyte professional, it describes the various players and strategies of the industry. For the student, it summarizes the key ideas of the most important cultural theorists introduced in advertising and marketing courses. For everyone, it helps explain the cultural, economic, and psychological role that advertising concepts play in society. A handy introduction for students and a quick reference for young professionals"--